Aluminum fluoride induced PdAu nanoparticles on layered g-C3N4 nanosheets for efficient dehydrogenation of formic acid at room temperature. (19th August 2022) - Zhou, Hong; Yang, Guang; Chen, Manyu; Liu, Youlin; Zhang, Zhongyuan; Hu, Yongji; Gu, Sasa; Wang, Jianhai; Shen, Yuesong
Abstract: We first develop the aluminum fluoride-induction strategy to construct PdAu nanoparticles combined with layered g-C3 N4 nanosheets (g-CNNS) by two-dimensional (2D) template approach. During the calcination process, g-CNNS are formed in the interlayer space of layered clay montmorillonite (MMT) template using melamine as precursor. After removing the MMT template by hydrofluoric acid, well-defined g-CNNS are obtained, accompanied by the formation of aluminum fluoride. Under the presence and induction of aluminum fluoride, PdAu alloy nanoparticles are uniformly dispersed on the surface of g-CNNS through the simple reduction process. Well-defined catalyst (PdAu/g-CNNS-AlF3 ) exhibits high catalytic performance for the decomposition of formic acid to hydrogen at room temperature, such as high catalytic activity (TOF: 2716 h −1 ) and high hydrogen selectivity (100%). These excellent catalytic activities are ascribed to the high specific surface area, unique 2D nanosheets architecture, and uniformly dispersed PdAu nanoparticles. This AlF3 -induced strategy combined with 2D-template approach provides a new idea for the design of highly efficient heterogeneous catalysts. Highlights: g-CNNS are fabricated by lamellar confinement of layered clay. PdAu nanoparticles are uniformly distributed on g-CNNS nanosheets under the induction of AlF3 . PdAu/g-CNNS-AlF3 exhibits high catalytic performance for the decomposition of formic acid. The high catalytic activities are ascribed to unique 2D architecture and uniformly dispersed PdAu nanoparticles.